Analysis of the Influence of the Type of Belt on the Energy Consumption of Transport Processes in a Belt Conveyor - Mirosław Bajda; Monika Hardygóra (Energies, 2021)
Results of tests into the energy-efficiency of belt conveyor transportation systems indicate that the energy consumption of their drive mechanisms can be limited by lowering the main resistances in the conveyor. The main component of these resistances is represented by belt indentation rolling resistance. Limiting its value will allow a reduction in the amount of energy consumed by the drive mechanisms. This article presents a test rig which enables uncomplicated evaluations of such rolling resistances. It also presents the results of comparative tests performed for five steel-cord conveyor belts. The tests involved a standard belt, a refurbished belt and three energy-saving belts. As temperature significantly influences the values of belt indentation rolling resistance, the tests were performed in both positive and negative temperatures. The results indicate that when compared with the standard belt, the refurbished and the energy-efficient belts generate higher and lower indentation rolling resistances, respectively. In order to demonstrate practical advantages resulting from the use of energy-saving belts, this article also includes calculations of the power demand of a conveyor drive mechanism during one calendar year, as measured on a belt conveyor operated in a mine. The replacement of a standard belt with a refurbished belt generates a power demand higher by 4.8%, and with an energy-efficient belt—lower by 15.3%.